Utilization chicken bones (Gallus gallus domesticus) into gelatin using extraction methods - Hilwatullisan; Syakdani, Adi; Khairunnisa, Eka Nurriza (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aimed to produce gelatin from chicken bones using different acid solvents and soaking times, and to evaluate the quality of the resulting gelatin according to SNI standards. Chicken bones were soaked in 6% HCl, 4% CH?COOH, 7% H?PO?, 0.3 M citric acid, and lime extract for 24 and 48 hours, and then extracted using a water bath at 75°C for 6 hours. The resulting gelatin was analysed for yield, moisture content, ash content, pH, protein content, organoleptic tests (colour and aroma), and FTIR spectrum. The results showed that all types of solvents could produce gelatin that met several quality parameters as specified in SNI 06-3735-1995. FTIR results for the H?PO? sample showed the presence of characteristic gelatin functional groups, namely 3184.32 cm?¹ (Amide A), 1646.58 cm?¹ (Amide I), 1456.74 cm?¹ (Amide II), 1173.34 cm?¹ (Amide III), indicating the successful conversion of collagen into gelatin. The optimal condition was obtained at In the treatment using lime extract with a soaking time of 48 hours, it produced a yield of 3.31%, moisture content of 2.49%, ash content of 1.12%, pH of 4.00, protein content of 79.94%, and the best organoleptic values with scores of 3.20 for color, 1.9 for aroma, and 1.23 for texture. This study indicates that lime can be an effective, environmentally friendly alternative solvent for gelatin production from chicken bone waste. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and ProductionSDG 9: Industry, Innovation, and InfrastructureSDG 3: Good Health and Well-beingSDG 13: Climate Action